The Advent of Modern Irish Drama and the Abjection of Peasant Popular Culture: Folklore, Fairs and Faction Fighting - Phelan, Mark (Archīum Ateneo, 2024)
This paper is part of a larger project in which the author is interested in recovering popular performative traditions and practices that have been occluded by the modernist project of the Irish Revival. This erasure has been compounded by subsequent historiographical paradigms that have reinforced the revivalist narrative of theatre history and excluded indigenous forms, traditions and practices (mumming, rhymers, strawboys) along with the wider performative culture of patterns, wakes, fairs, faction fights etc. This essay subjects to scrutiny what the author sees as a disjuncture between the riotous reality of peasant popular culture and its representation in Revivalist dramas to argue that Irish Theatre Studies needs to develop alternative historiographies of performance and to methodologically engage with theoretical models extant in Performance Studies.